2014
DOI: 10.1002/ece3.985
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the distribution of Aspalathus linearis (Rooibos tea): implications of climate change for livelihoods dependent on both cultivation and harvesting from the wild

Abstract: Aspalathus linearis (Burm. f.) R. Dahlgren (rooibos) is endemic to the Fynbos Biome of South Africa, which is an internationally recognized biodiversity hot spot. Rooibos is both an invaluable wild resource and commercially cultivated crop in suitable areas. Climate change predictions for the region indicate a significant warming scenario coupled with a decline in winter rainfall. First estimates of possible consequences for biodiversity point to species extinctions of 23% in the long term in the Fynbos Biome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Hence, the AIWs may be closer to equilibrium in the invasive range than in the native range (Callen & Miller, ; Early & Sax, ; Strubbe, Broennimann, Chiron, & Matthysen, ). Niche divergence is strongly related to rapid evolution in the invasive range, disequilibrium in the native range caused by biotic interactions, dispersal barriers, and human activities (Ansong & Pickering, ; Dellinger et al., ; Guo, Lambertini, Li, Meyerson, & Brix, ; Lötter & Maitre, ; Marini et al., ; Martínez‐Cabrera, Schlichting, Silander, & Jones, ; Schmidt & Drake, ). Previous studies have shown that plant species for which dispersal ability is limited in native ranges could occupy wide climatic niche spaces enabled by genetic evolution and human activities (Donoghue & Edwards, ; Dellinger et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the AIWs may be closer to equilibrium in the invasive range than in the native range (Callen & Miller, ; Early & Sax, ; Strubbe, Broennimann, Chiron, & Matthysen, ). Niche divergence is strongly related to rapid evolution in the invasive range, disequilibrium in the native range caused by biotic interactions, dispersal barriers, and human activities (Ansong & Pickering, ; Dellinger et al., ; Guo, Lambertini, Li, Meyerson, & Brix, ; Lötter & Maitre, ; Marini et al., ; Martínez‐Cabrera, Schlichting, Silander, & Jones, ; Schmidt & Drake, ). Previous studies have shown that plant species for which dispersal ability is limited in native ranges could occupy wide climatic niche spaces enabled by genetic evolution and human activities (Donoghue & Edwards, ; Dellinger et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Lambertini, Li, Meyerson, & Brix, 2013;Lötter & Maitre, 2014;Marini et al, 2012;Martínez-Cabrera, Schlichting, Silander, & Jones, 2012;Schmidt & Drake, 2011). Previous studies have shown that plant species for which dispersal ability is limited in native ranges could occupy wide climatic niche spaces enabled by genetic evolution and human activities (Donoghue & Edwards, 2014;Dellinger et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial agriculture (particularly potato and rooibos tea farming), alien vegetation infestations, and extensive new housing developments are among the drivers of habitat transformation and biodiversity loss. Climate and impact models suggest that the increase in temperatures and decrease in winter rainfall predicted for could have far-reaching effects on the BM's terrestrial ecosystems, including reductions in water supply, sea level rise, species losses, and wildfire increases (Lötter et al 2014). As the municipality's economy is driven by agriculture and a growing eco-tourism sector, there is concern that climate change will have severe impacts on local livelihoods, compounded by the municipality's low literacy levels (70.5%) and the existence of very few alternative economic opportunities (BRM 2012).…”
Section: The Bergrivier Municipalitymentioning
confidence: 99%
“…Rooibos ( Aspalathus linearis ), an indigenous fynbos shrub of South Africa, is cultivated for the production of rooibos herbal tea, representing 10% of the global tea market . Demand surpasses production, a shortfall aggravated by drought and shrinking production areas as a result of climate change . This compels the industry to consider the potential of rooibos processing waste as a marketable product.…”
Section: Introductionmentioning
confidence: 99%